Lo gótico y neogótico. La imagen de los godos en De Rebus Hispaniae. De la Fuente Escribano, Alejandro. Madrid, Dykinson Ebook, 2023, 324 pp. ISBN: 978-84-1170-981-1 - Castillo Lozano, José Ángel (Antigüedad y Cristianismo, 2026)
.